2017
DOI: 10.1242/jeb.152314
|View full text |Cite
|
Sign up to set email alerts
|

Flipper stroke rate and venous oxygen levels in free-ranging California sea lions

Abstract: The depletion rate of the blood oxygen store, development of hypoxemia and dive capacity are dependent on the distribution and rate of blood oxygen delivery to tissues while diving. Although blood oxygen extraction by working muscle would increase the blood oxygen depletion rate in a swimming animal, there is little information on the relationship between muscle workload and blood oxygen depletion during dives. Therefore, we examined flipper stroke rate, a proxy of muscle workload, and posterior vena cava oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 31 publications
4
24
1
Order By: Relevance
“…Based on our review of heart rate regulation during exercise, we find that most investigators consider the increase in heart rate at the initiation of exercise and at workloads up to 60% of maximal oxygen consumption to be mediated via the parasympathetic system (Borresen and Lambert, 2008;Carter et al, 2003). Given that (1) exercise is often initiated after prolonged glides in marine mammals, (2) peak post-dive metabolic rates of Weddell seals (Leptonychotes weddellii) are only about twice resting metabolic rate, far less than 60% maximal oxygen consumption, and (3) field metabolic rates and stroke rates of diving sea lions are typical of those of sea lions swimming in a flume at ≤50% maximal oxygen consumption, we postulate that any exercise modulation of heart rate during dives occurs primarily via the parasympathetic system (Costa et al, 1991;Feldkamp, 1987a,b;Ponganis et al, 1991;Tift et al, 2017;Williams et al, 2000Williams et al, , 2004. Furthermore, in a study of freediving muskrats, the increase in heart rate owing to underwater exercise (swimming against a current) and the increase in heart rate during final ascent were both mediated by parasympathetic withdrawal (Signore and Jones, 1996).…”
Section: Parasympathetic-sympathetic Tone During Divesmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on our review of heart rate regulation during exercise, we find that most investigators consider the increase in heart rate at the initiation of exercise and at workloads up to 60% of maximal oxygen consumption to be mediated via the parasympathetic system (Borresen and Lambert, 2008;Carter et al, 2003). Given that (1) exercise is often initiated after prolonged glides in marine mammals, (2) peak post-dive metabolic rates of Weddell seals (Leptonychotes weddellii) are only about twice resting metabolic rate, far less than 60% maximal oxygen consumption, and (3) field metabolic rates and stroke rates of diving sea lions are typical of those of sea lions swimming in a flume at ≤50% maximal oxygen consumption, we postulate that any exercise modulation of heart rate during dives occurs primarily via the parasympathetic system (Costa et al, 1991;Feldkamp, 1987a,b;Ponganis et al, 1991;Tift et al, 2017;Williams et al, 2000Williams et al, , 2004. Furthermore, in a study of freediving muskrats, the increase in heart rate owing to underwater exercise (swimming against a current) and the increase in heart rate during final ascent were both mediated by parasympathetic withdrawal (Signore and Jones, 1996).…”
Section: Parasympathetic-sympathetic Tone During Divesmentioning
confidence: 97%
“…Thus, pulmonary stretch receptors would not appear to have a role in this initial increase in heart rate during the bottom phases of these two dives. Exercise may exert an effect, especially because prolonged glides end at the start of the bottom phase of deep dives (Tift et al, 2017). Although difficult to evaluate, the increase in heart rate may also be secondary to volitional control at the start of the bottom phase and ascent phase of the dive.…”
Section: Parasympathetic-sympathetic Tone During Divesmentioning
confidence: 99%
“…Although all three variables may have influenced at‐sea FMR, dive depth may have been the primary driver given that (1) dive depth has an influence on dive duration but the opposite is not necessarily true (i.e., it takes more time for sea lions to reach deeper depths but they can have long duration dives that are irrespective of depth), and (2) our initial exploratory plots between at‐sea FMR and each individual variable showed no apparent relationship between the bout duration of mixed strategy foragers and at‐sea FMR (i.e., bout duration appeared more influential for deep‐diving sea lions). The finding that at‐sea FMR increased with dive depth was unexpected given a previous study that found the opposite relationship (Costa & Gales, ) and because of energy‐saving swim strategies associated with changes in buoyancy that air‐breathing marine predators use on deeper dives, such as stroke‐and‐glide swimming (Crocker, Gales, & Costa, ; Tift, Hückstädt, McDonald, Thorson, & Ponganis, ; Watanuki, Niizuma, Gabrielsen, Sato, & Naito, ; Williams et al., ). Tift et al.…”
Section: Discussionmentioning
confidence: 86%
“…McDonald and Ponganis () found the dive response, characterized by extreme bradycardia (<10 beats/min), of California sea lions was pronounced on longer dives (68% of dives >4 min and 98% of dives >5 min), but more variable on short dives (<3 min) where only 43% of dives had heart rates below resting. Similarly, blood flow to swimming muscles appears to be restricted during dives >100 m but is not consistently regulated during shallower dives in this species (Tift et al., ). Sea lions using the deep‐diving strategy generally had a much greater percentage of long duration dives, with an average of 51% of dives >4 min and 46% >5 min compared with mixed strategy foragers that only had an average of 24% of dives >4 min and 14% >5 min.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation